(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper presents a comparative control performance study based on different combinations of classical proportional-integral (PI) and intelligent fuzzy logic controllers. The control settings were used to control both active and reactive powers to achieve the optimum operation of a double-feed induction generator (DFIG) integrated into a wind power conversion system with maximum power point tracking (MPPT). For this purpose, a mathematical model of the conversion system (wind turbine-DFIG) is established. The active and reactive powers at the output of the DFIG are controlled separately to achieve a better power factor. The complete model of the wind energy conversion system is simulated and tested in the Matlab-Simulink environment. The results obtained are compared to PI controllers. The study clearly shows the effectiveness of introducing the fuzzy technique in the control loops.